The FH phenotype: monogenic familial hypercholesterolaemia, polygenic dyslipidaemia and other causes - Mariano, C. (2019)
Introduction: (i) Cardiovascular disease (CVD), particularly coronary heart disease (CHD) and stroke, are the leading cause of morbidity and mortality worldwide; (ii) Dyslipidaemia is an important but modifiable cardiovascular risk factor. For instance, Familial Hypercholesterolaemia (FH) is a monogenic autosomal condition where patients present very high LDL-C values and an increase cardiovascular risk; (iii) FH is caused by mutations in 3 genes: LDLR, APOB and PCSK9. However in only about 40%-50% of the cases an FH causing mutation is found.